“Incidencia Del Entorno Familiar En El Desarrollo Del Saber Ser, De Los Estudiantes De Octavo De Educación Básica Y Primero De Bachillerato De La Unidad Educativa Barreiro, De La Parroquia Barreiro, Cantón Babahoyo, Provincia De Los Ríos. - García Murrieta, Blanca (2015)
Every day society demands more power and precision parents of families and educational institutions the formation of the personality of students, the quality of education depends not only on knowledge and skills developed in the curriculum but also in the interest and values learned in the family environment governing its action, love, responsibility, honesty, values which are essential regulators to structure a family with human quality and know-being and prevent family spread in this direction have values individual existence, an existence above individually since it is part of social reality as meanings relationship between the facts of social life and the needs of society, both the transcendental values for an organized family, are applying their equality members, as a rule La justice peaceful and harmonious coexistence, which gives us a love of life, so we internalize the new members of society who make a home is not just about the social conditions but know that the family is a core society as a motivational trainer personality that directs efforts towards meeting their needs, when values constitute grounds for the action of the subject become true regulators of their behavior, this has important implications for educational policy, on which allow us to understand the formation of values in school and college is not limited to a single homogeneous linear transformation of information from teacher to student, but results in a complex process of communication between teachers and students in the teaching-learning process where the student takes an active ownership in the individual appropriation of meaning for the construction of their personal values and form a true family organized. .